A new sensing platform based on NH2fMWCNTs for the determination of antiarrhythmic drug Propafenone in pharmaceutical dosage forms - Nawar, Amir Shaaban Farag Moham; Bakirhan, Nurgul K.; Švancara, Ivan; Ozkan, Sibel A. (Elsevier Science Inc., 2019)
A novel sensor based on a modification of glassy carbon electrode (GCE) with NH2-functionalized multi walled carbon nano-tubes (NH(2)fMWCNTs) is reported and its applicability to the electrochemical sensing of Propafenone (PPF) demonstrated. The electrochemical catalytic activity was also utilized as a sensitive detection method for the investigation of the detailed redox mechanism of PFF using cyclic and and differential pulse voltammetry. The surface morphology of the sensor was investigated by SEM armed with EDX probe. Electrochemical impedance spectroscopy was employed as well to define the electron transfer capability of modified and bare electrodes. Key experimental and instrumental conditions related to electrochemical determination by cyclic, differential pulse, and square wave voltammetry, such as amount of modifier, pH, scan rate, accumulation time and potential were studied and optimized. The results have shown a significant enhancement of the peak current after modifying the electrode; the calibration curves of PPF offering good linearity from 0.1 to 10 mu M, limit of quantification (LOQ) being 0.03 mu M and limit of detection (LOD) 0.01 mu M, both when using DPV technique. The proposed sensor was successfully applied to the determination of PFF in dosage form without any special purification, separation or pre-treatment steps. The results of analyses obtained with the proposed sensor were satisfactory and fully statistically relevant. (C) 2019 Elsevier B.V. All rights reserved.
Nová analytická platforma založená na NH2fMWCNT pro stanovení antiarytmika Propafenonu ve farmaceutických přípravcích
Keywords: electrochemistry; glassy carbon electrode; nanotubes; propafenone; drug analysis; elektrochemie; elektroda ze skelného uhlíku; nanotrubice; propafenon; analýza léčiv